Hubungan Penggunaan Alat Kontrasepsi Hormonal terhadap Hipertensi di Wilayah Kerja Puskesmas Grogol - Widiawatie, Noni; , Sulastri, S.Kp., M.Kes (2017)
creating a prosperous man Indonesia in addition to education and health programs. One of the health problems often experienced by hormonal contraceptive acceptors are weight gain, dizziness and hypertension or high blood pressure certainly hormonal contraceptive use has several benefits in addition to complaints and side effects appear. Hypertension is known as the silent killer because there are generally no manifestation for patients, if this condition is left, it can interfere with the function of other organs, especially such vital organs, namely the heart and kidneys. The results of observations conducted by researchers 15 people who have hypertension or high blood pressure. Objective: To examine the relationship hormonal contraceptive use against hypertension in Puskesmas Grogol. Methods: The study used cross sectional design. The population studied were mothers who used hormonal contraception in Puskesmas Grogol, amounting to 75 people. Collecting data using questionnaires, blood pressure checks and data analysis using statistical test Chi Square. Result: The Chi Square test results obtained 2 hitung value of 7.324 with a significance value (p-value) of 0.026 Conclusion: There is a relationship between hormonal contraceptive use against hypertension with significant value of less than 0.05.